Mountain Riverine Floods in Ecuador: Issues, Challenges, and Opportunities - Pinos, Juan; Timbe, Luis (Frontiers in Water, 2020)
Increasing urbanization and development along rivers, together with climate change, exacerbate future flood risk in Ecuador. Current policy strategies in the highlands greatly need improvement. Politicians must rethink if the governmental environmental institutions and inhabitants of the highlands are prepared to respond to future small- and large-scale flood episodes. The purpose of this paper is to identify the issues facing flood risk management (FRM) in the Ecuadorian highlands with a view to finding approaches for overcoming them. We focus on three specific concerns: an assessment of the deficiencies of current flood risk management, the development of diverse strategies to combat flooding, and the need for an overarching vision for future actions and research. These are presented within a theoretical framework together with the authors’ recommendations of adaptation options for Ecuador’s newly emerging flood challenges. Traditional and novel flood risk management approaches are required, including smart land-use planning, implementation of structural and non‐structural measures, coordinated water governance systems with public participation, and the development and improvement of resilience to flooding. Moreover, academic input is a fundamental component of FRM to fill current knowledge gaps regarding mountain floods. This article addresses further research developments that are required to articulate and enable targeted FRM. To our knowledge, no previous publication has specifically dealt with FRM issues in the Ecuadorian highlands, thus, an overview of the current status of FRM is necessary. It is hoped that the challenges associated with flood management discussed here can be addressed over time.